Scrofula: emergency department presentation and characteristics - Forget, Nicolas (Springer-Verlag, 2009)
BACKGROUND: In the US, scrofula is generally uncommon, but it may be the manifestation of disseminated tuberculosis in immunocompromised patients. Given the delay to obtain PPD results, AFB results, and cultures for TB, the emergency physician (EP) must rely on the history and physical examination to make the diagnosis of scrofula. AIMS: To illustrate a set of criteria that would be useful to the emergency physician to identify cases of scrofula. METHODS: We retrospectively reviewed the charts of patients with a final diagnosis of scrofula at our institution to identify the characteristics of patients who present to the emergency department with a neck mass that was eventually diagnosed as scrofula. RESULTS: We found that being foreign born, being HIV+, and having a prior history of a positive PPD appeared to be associated with a diagnosis of scrofula. CONCLUSIONS: This review suggests that scrofula should be included in the EP’s differential diagnosis of neck in masses when patients present subacutely and they have significant TB risk factors. In such cases, the EP should strongly consider ruling out pulmonary TB.